이용자 관점에서 본 수원법원 종합신청사 사인시스템에 관한 연구 - 황유철; You-chul Hwang (한국디자인포럼, 2019)
연구배경 최근 들어 공공청사는 대형화되고 기존 행정 및 공공의 목적 등 다양한 요구에 의하여 그 이용자가 늘어가고 있다. 따라서 공공청사 이용자에 대한 보다 정확하고 편리한 사인시스템이 적용되어야 한다. 본 연구는 이용자관점에서 공공청사, 특히 법원의 안내 사인시스템을 연구하여 효율적인 방안을 제시하고자 한다. 연구방법 이를 위해 먼저 국내 법원중 규모가 큰 서울, 부산, 인천의 사례를 연구 분석하고, 다음으로 인천국제공항과 일반인들이 많이 찾는 국립중앙도서관 그리고 부산도시철도 다대선 사례를 비교 분석하기로 한다. 효율적인 분석을 위하여 대상 사례를 직접 방문 조사하고 관련 학술자료를 검토한 후, 통계청 통계자료를 통해 보다 객관적으로 분석하기로 한다. 연구결과 국내 법원 사인시스템의 사례분석과 수원법원 대상지 분석을 통하여 이용자 중심의 사인시스템을 연구하였다. 그러나 관습적으로 설계하는 사인시스템은 사례의 문제점을 해결하지 못하고 대상건물에 그대로 적용되어 있었다. 또한 국내는 물론 아시아 최대 규모의 법원이라는 규모만 강조되고 효율적인 사인시스템이 적용되지 못한 문제점을 나타내고 있다. 결론 수원법원 종합신청사는 차량과 보행자 각각의 동선을 고려하지 않은 사인의 위치와 크기, 색상, 문자로 적용되어 있었다. 그러므로 이용자 중심의 사인디자인시스템으로 적용하는 변화가 요구되었다. 그리고 민간에서 활발히 사용되고 있는 디지털 사인시스템 적용도 필요하다고 생각한다. 나아가 VR, AR, 홀로그램 기술을 도입한 신 개념 사인시스템을 부분적으로 라도 도입되기를 희망한다. 본 연구가 공공청사는 항상 민간 부분보다 디자인이 실용적이지 못하고, 신 개념 디자인을 신속하게 반영하지 못하는 일반적인 인식을 개선하는 기초자료가 되기를 기대한다. Background We will study and analyze the importance of the public office sign system, and examine the user-centered sign system. In recent, public offices have become larger, and the number of users has been increasing due to various demands as well as administrative and public purposes. Therefore, a more accurate and convenient sign system should be applied to public government users. Therefore, this study intends to propose an effective method by studying the system of the public office, especially the court. Method We analyze the cases of Seoul, Busan and Incheon, which are large in domestic courts, and analyze the case of Incheon International Airport, which is a multi - use facility, and the National Central Library, which is popular among the general public, and the recently reopened Busan metro sign system. For efficient analysis, we will visit the case study, review the related academic data, and analyze more objective data through statistical data. Based on the case analysis, we will study the application method of efficiency by comparing and analyzing the objective of the research subject from the viewpoint of efficient application of the sign system. Result We analyzed the focused user sign system through case analysis and site analysis. However, a conventional sign system does not solve the problem of the case and is applied to the target building as it is. In addition, the scale of the biggest court in Asia as well as the country is emphasized, and it shows the problem that the efficient sign system is not applied. Conclusion The public office needs to change from a general view that it is always lagging behind the private sector, but rather to a more user-centered system by applying new technologies to the forefront. In this study, we propose a digital sign system which is actively used in the private sector, and further suggest a new concept sign system using VR, AR and hologram technology.